1998
DOI: 10.1515/bchm.1998.379.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Analyses of the Domain Architecture of Mammalian Protein Disulphide-Isomerase

Abstract: The high resolution structure of full-length protein disulphide-isomerase (PDI) has not been determined, but the polypeptide is generally assumed to comprise a series of consecutive domains. Models of its domain organisation have been proposed on the basis of various sequence-based criteria and, more recently, from structural studies on recombinant fragments corresponding to putative domains. We here describe direct studies of the domain architecture of full-length mammalian PDI based on limited proteolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…Previously we showed that limited proteolysis of full length bovine PDI results in the formation of fragments in which the x region was associated either with the b' domain or with the a' domain, but that cleavage at an internal site in the x region was never observed 23 . This implies that the x region is structured and that this structure can be associated with either of the adjacent domains.…”
Section: Evidence For Alternative Conformations Of the X Region In Fumentioning
confidence: 98%
“…Previously we showed that limited proteolysis of full length bovine PDI results in the formation of fragments in which the x region was associated either with the b' domain or with the a' domain, but that cleavage at an internal site in the x region was never observed 23 . This implies that the x region is structured and that this structure can be associated with either of the adjacent domains.…”
Section: Evidence For Alternative Conformations Of the X Region In Fumentioning
confidence: 98%
“…PDI is an essential protein that is organized structurally in four thioredoxin domains and catalyzes the transfer of disulfide bonds to substrate proteins via a CX2C active center (37,53,115). The redox state of PDI is determined by the essential protein Ero1, a flavin bound membrane associated protein (36,43,92).…”
Section: The Endoplasmic Reticulummentioning
confidence: 99%
“…3). 55) Domains a and a' have a catalytically active Cys-Gly-His-Cys motif, while b and b' domain do not have catalytic activity. The order of the domains is a-b-b'-x-a'-c, where x is a linker region between b' and a' 56) and c is a Cterminal acidic α-helix containing the ER retention signal.…”
Section: The Domain Structure Of Pdimentioning
confidence: 99%